2021
DOI: 10.1098/rsta.2021.0115
|View full text |Cite
|
Sign up to set email alerts
|

Data science approaches to infectious disease surveillance

Abstract: Novel data science approaches are needed to confront large-scale infectious disease epidemics such as COVID-19, human immunodeficiency viruses, African swine flu and Ebola. Human beings are now equipped with richer data and more advanced data analytics methodologies, many of which have become available only in the last decade. The theme issue Data Science Approaches to Infectious Diseases Surveillance reports the latest interdisciplinary research on developing novel data science methodo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Some mutations at critical locations of the genetic sequence may change the virus’s transmissibility and severity. Here we extend the multiple-strain model 35 , 36 , 41 to characterize viral evolutionary dynamics. For country i , such dynamics are captured by the transmissibility matrix , the severity matrix and the mutation matrix , all with dimensions M × M .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some mutations at critical locations of the genetic sequence may change the virus’s transmissibility and severity. Here we extend the multiple-strain model 35 , 36 , 41 to characterize viral evolutionary dynamics. For country i , such dynamics are captured by the transmissibility matrix , the severity matrix and the mutation matrix , all with dimensions M × M .…”
Section: Methodsmentioning
confidence: 99%
“…, M }, respectively. We set a country-specific severity matrix to account for the heterogeneity in the health-care burden of COVID-19 and the age structure in different countries (Supplementary Note 3 ) 41 , 49 , 50 . We assume a linear strain space and local movement by a one-direction stepwise mutation in the model 47 .…”
Section: Methodsmentioning
confidence: 99%
“…During the outbreak of the COVID-19 pandemic, predictive data science techniques using real-time data were very fundamental in both disease surveillance, digital contact tracing, diagnosis, predicting the magnitude and impact of expanded outbreak. Data scientists have shown that by joining with medicine and public health scholars they can identify, analyze and model traditional and novel data generated by, or associated with, the pandemic to produce rich understandings [41]. These similar approaches are very relevant to monitoring, evaluation and learning because of the opportunity they present to have access to timely data, use of data of good quality and the power of data science techniques to quickly generate the required insights for decision making or making adaptations.…”
Section: Recommendationsmentioning
confidence: 99%
“…Variable transformation provides an approach in solving problems such as distribution and linear characteristics [20]. Owing to the progress in multiple disciplines, including computer science, data science, applied mathematics, and statistics, we have moved closer to innovative data science approaches to obtain significant viewpoints in disease incidence and management [21][22][23][24]. There have been studies that identified the contribution of variable transformation in applications.…”
Section: Introductionmentioning
confidence: 99%